2017
DOI: 10.21037/tau.2017.03.60
|View full text |Cite
|
Sign up to set email alerts
|

Robot-assisted microsurgery for chronic orchialgia

Abstract: Chronic orchialgia is one of the most common complaints seen in the urologists office and has traditionally been considered a very difficult diagnostic and therapeutic challenge for the clinician. First line management of chronic orchialgia is conservative treatment; however, in men who fail conservative therapy, surgical intervention may be indicated. Microsurgery has been the mainstay for surgical treatment of chronic orchialgia, but the implementation of robotics to microsurgery lends itself particularly to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…28 In a recent review Korzadeh reported that inguinal hernia repair with use of mesh in bilateral open and/or laparoscopic repair may cause male infertility for the obstruction and/or damage to the cord and the vessels. 29 It is quite innovative that, a recent article proposes the use of an operating microscope in the treatment of inguinal hernia, especially when employed by an urologist performing simultaneous operations for varicocele or surgical procedures on spermatic cord or testis.…”
mentioning
confidence: 99%
“…28 In a recent review Korzadeh reported that inguinal hernia repair with use of mesh in bilateral open and/or laparoscopic repair may cause male infertility for the obstruction and/or damage to the cord and the vessels. 29 It is quite innovative that, a recent article proposes the use of an operating microscope in the treatment of inguinal hernia, especially when employed by an urologist performing simultaneous operations for varicocele or surgical procedures on spermatic cord or testis.…”
mentioning
confidence: 99%
“…74 Others have used the magnified 3D view that the robotic system offers to perform a variety of microsurgical procedures, including varicocelectomy, vasectomy reversal, spermatic cord denervation and testicular sperm extraction. 75 So far these have not exhibited superiority over the use of an operating microscope to justify the high cost.…”
Section: The Increased Cost Of the Robotic System And Maintenance Is mentioning
confidence: 99%
“…One study reported that the group tried to come to an understanding with its community‐based hospital to use the robot in slots when there was less use, such as early morning and late afternoon. It was argued that the average per‐case added cost was reduced when more patients underwent robotic surgery …”
Section: New Inventions In Microscopic Vasovasostomy and Vasoepididymmentioning
confidence: 99%
“…It was argued that the average per-case added cost was reduced when more patients underwent robotic surgery. 66 As…”
Section: Robot-assisted Vasovasostomy and Vasoepididymostomymentioning
confidence: 99%